Abram as portas da ciência para os mestres e as mestras passarem: a ressignificação da Jurema no Acervo José Simeão Leal - Almeida, Carla Maria de (2017)
The present work aims to understand how the information contained in the documents which constitutes the José Simeão Leal Collection contributes to the construction of the Jurema memories in the state of Paraíba. In assuming, in the 1940’s, the position in the Administrative Department of Public Service of the state of Paraíba, the doctor and intellectual José Simeão Leal José has focused in researching and registering the manifestations of popular culture of his state. In the midst of this study, informations were collected on the Jurema, Afro-Indian religiosity. The collected documents are in the form of photographs, a drawing, typewritten and manuscripts. Also, there are correspondences received by researchers on the subject, such as Roger Bastide. The documentation is in the José Simeão Leal Collection, located, since 2009, in the Núcleo de Documentação e Informação Histórico Regional. The collection constitutes both a space of memory of José Simeão Leal himself and of the people and practices that have had contact with him and left traces in his life, such as the religious and rituals of Jurema recorded in his research. We understand the importance of the sources for the construction of the memorialistic narrative of the religious / Afro-indigenous in Paraíba taking as theoretical-methodological foundation the studies inserted in the field of social sciences, specifically Information Science, which deal with social memory, Culture, identity, and documents used as memory mediums (ASSMANN, 2011), in addition to research on religion. The methodological assumptions are based on documentary analysis (ARÓSTEGUI, 2006) and, since the image, especially photography, constitutes the main document of the study, the resources of semiotics (SANTAELLA and NÖTH, 1997) directed the analysis of this documentary type. The documents about Jurema in the personal archive reveal the ethnographic methodology of the research of José Simeão Leal, as well as the complexity and richness of this religiosity, with a diversity of ritual, ornamentation, entities, objects, musicalities and spaces.